2014
DOI: 10.1016/j.jconrel.2014.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Neutral polymer micelle carriers with pH-responsive, endosome-releasing activity modulate antigen trafficking to enhance CD8+ T cell responses

Abstract: Synthetic subunit vaccines need to induce CD8+ cytotoxic T-cell (CTL) responses for effective vaccination against intracellular pathogens. Most subunit vaccines primarily generate humoral immune responses, with a weaker than desired CD8+ cytotoxic T-cell response. Here, a neutral, pH-responsive polymer micelle carrier that alters intracellular antigen trafficking was shown to enhance CD8+ T-cell responses with a correlated increase in cytosolic delivery and a decrease in exocytosis. Polymer diblock carriers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 49 publications
4
115
1
Order By: Relevance
“…The final composition of the first block consisted of 92 mole % PEGMA along with 8 mole % PDSM which has been found to be a sufficient amount of pyridyl disulfide moieties for antigen conjugation by other nanocarriers that have been used for in vivo applications. 43, 45, 60 …”
Section: Resultsmentioning
confidence: 99%
“…The final composition of the first block consisted of 92 mole % PEGMA along with 8 mole % PDSM which has been found to be a sufficient amount of pyridyl disulfide moieties for antigen conjugation by other nanocarriers that have been used for in vivo applications. 43, 45, 60 …”
Section: Resultsmentioning
confidence: 99%
“…Keller et al showed how pH-responsive micelles significantly enhance cytotoxic T lymphocyte responses, in comparison to micelles without these properties [117]. This effect was achieved because the forming polymers are protonated at endosomal pH which allows them to interact with the membrane and disrupt the endosome [117,118]. The same tendency was reported in the case of pH-sensitive liposomes, cationic liposomes and bioreducible linkages [119122].…”
Section: Access Of Nanostructures To Target Cellsmentioning
confidence: 93%
“…This endosomal escape can be promoted by the disruption of the endosome membrane, as discussed by several authors [115,116]. Keller et al showed how pH-responsive micelles significantly enhance cytotoxic T lymphocyte responses, in comparison to micelles without these properties [117]. This effect was achieved because the forming polymers are protonated at endosomal pH which allows them to interact with the membrane and disrupt the endosome [117,118].…”
Section: Access Of Nanostructures To Target Cellsmentioning
confidence: 99%
“…The proton sponge effect is observed with nanoparticles that have a high buffering capacity, as the influx of ions and water into the endosomes leads to high osmotic pressure, and eventually rupture of the organelle [46]. Keller et al have also reported the use of a pH-sensitive polymer micelle nanoparticle for cytosolic delivery of antigens, and demonstrated higher concentrations of antigen-specific cytotoxic T cells compared to controls [47]. …”
Section: Antigen Delivery and Presentationmentioning
confidence: 99%